Hubungan Antara Stres Kerja dan Keluhan Nyeri Punggung Bawah Pekerja Las Industri Pembuatan Kapal - Dwidyah Laurensyah Heriyanto Putri; Endang Dwiyanti; Susy Katikana Sebayang (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Low Back Pain (LBP) is a widespread health issue that profoundly impacts workers' productivity and quality of life. In addition to non-specific health effects, LBP can result in long-term disability and considerable economic losses. Globally, LBP affects 619 million individuals, with projections suggesting an increase to 843 million by 2050, particularly Low Middle Income Countries (LMICs) in Asia and Africa. The shipbuilding industry, known for its physically strenuous tasks and stringent deadlines, presents unique ergonomic challenges that can exacerbate job-related stress and precipitate the onset of LBP. This study examines Project X PT Y, a pivotal entity in Indonesia's shipbuilding sector. Utilizing a quantitative methodology and a cross-sectional research design, the study encompasses all 26 workers from the welding workshop at Project X PT Y. The analysis, conducted using the Spearman test, reveals a robust monotonic relationship between work-related stress and LBP complaints, indicating that the incidence of LBP increases concomitantly with elevated work stress.